2020
DOI: 10.2147/jpr.s254275
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Comparison of Full-Endoscopic and Microscopic Unilateral Laminotomy for Bilateral Decompression in the Treatment of Elderly Lumbar Spinal stenosis: A Retrospective Study with 12-Month Follow-Up</p>

Abstract: Although lumbar spinal stenosis (LSS) is the most common spinal disease in the elderly, there is still a confusion about the appropriate surgical treatment strategy. The aim of this study was to compare the safety and efficacy of full-endoscopic and microscopic unilateral laminotomy for bilateral decompression (ULBD) for LSS in elderly patients. Patients and Methods: A retrospective analysis of 61 consecutive elderly patients with LSS who underwent either full-endoscopic (FE group) or microscopic (Micro group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
1
17
0
3
Order By: Relevance
“…The total prevalence of complications and revision procedures was similar to that reported previously. 12,24,29,30 The success rate of FELDS reached 86.55%, which was similar to that for ODFS. Furthermore, we undertook FELDS to treat LSS at a relatively earlier phase; a lack of experience and appropriate instruments could lead to a prolonged procedure, neural injury, and insufficient decompression.…”
Section: Complications and Influencing Factorssupporting
confidence: 71%
“…The total prevalence of complications and revision procedures was similar to that reported previously. 12,24,29,30 The success rate of FELDS reached 86.55%, which was similar to that for ODFS. Furthermore, we undertook FELDS to treat LSS at a relatively earlier phase; a lack of experience and appropriate instruments could lead to a prolonged procedure, neural injury, and insufficient decompression.…”
Section: Complications and Influencing Factorssupporting
confidence: 71%
“…The ULBD technique was first reported by Young in 1988, and it has been rapidly improved by the use of various minimally invasive techniques, such as microscopy and microendoscopy. Nevertheless, the air medium required under microscopy and microendoscopy cannot provide a clear visual field, especially in contralateral decompression procedures ( 4 , 5 ). Full endoscopic ULBD can achieve effective bilateral decompression via water medium, and several studies have reported favorable outcomes from this version of the procedure in the treatment of LSS ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the air medium required under microscopy and microendoscopy cannot provide a clear visual eld, especially in contralateral decompression procedures. [4,5] Full endoscopic ULBD can achieve effective bilateral decompression via water medium, and several studies have reported favorable outcomes from this version of the procedure in the treatment of LSS. [6] However, full endoscopic ULBD has a steep learning curve and a high rate of complications.…”
Section: Discussionmentioning
confidence: 99%